The Effectiveness of English Animated Videos in Enhancing the Vocabulary - Yetti, Dzulhijjah; Yelmi, Harmi; Nurbit, Nurbit; Akbar, Rahmad; Nofiar, Andri (Universitas Pahlawan Tuanku Tambusai, 2024)
The issue addressed in this study is the low ability of children to recognize English vocabulary. There is a lack of variation in the use of teaching media for vocabulary instruction. The research questions are as follows: first, does the use of animated videos enhance children's ability to recognize English vocabulary? Second, how can animated videos be utilized to improve vocabulary recognition? The aim of this research is to improve early childhood vocabulary recognition in English through the use of animated videos, as well as to evaluate the effectiveness of these videos in vocabulary instruction at SDN 020 Ridan Permai for the 2024/2025 academic year. The method employed in this study is Classroom Action Research (CAR) based on the model developed by Kemmis and McTaggart. The subjects of this study consist of 28 students. Data were collected using both test and non-test methods.